Network Performance Test and Analysis of LTE-V2X in Industrial Park Scenario. (7th December 2020) - Fan, Yuanyuan; Liu, Liu; Dong, Shuoshuo; Zhuang, Lingfan; Qiu, Jiahui; Cai, Chao; Song, Meng
Abstract : As one of the mainstream technologies of vehicle-to-everything (V2X) communication, Cellular-V2X (C-V2X) provides high reliability and low latency V2X communications. And with the development of mobile cellular systems, C-V2X is evolving from long-term evolution-V2X (LTE-V2X) to new radio-V2X (NR-V2X). However, C-V2X test specification has not been completely set in the industry. In order to promote the formulation of relevant standards and accelerate the implementation of industrialization, the field test and analysis based on LTE-V2X in the industrial park scenario is conducted in this paper. Firstly, key technologies of LTE-V2X are introduced. Then, the specific methods and contents of this test are proposed, which consists of functional and network performance tests to comprehensively evaluate the communication property of LTE-V2X. Static and dynamic tests are required in both line-of-sight (LOS) and non-line-of-sight (NLOS) scenarios to evaluate network performance. Next, the test results verify that all functions are normal, and the performance evaluation indexes are appraised and analyzed. Finally, it summarizes the whole paper and puts forward the future work.